HUBUNGAN PERILAKU ASERTIF PERAWAT DALAM MEMBERIKAN PELAYANAN DENGAN TINGKAT KEPUASAN PASIEN - Leni Wijaya; Tresia Francica (Jurnal Kesehatan dan Pembangunan, 2026)
Assertive behavior in nurses is a crucial aspect of therapeutic communication that can significantly influence the quality of care and patient satisfaction. This studyaims to examine the relationship between nurses' assertive behavior in delivering care and the level of patient satisfaction at the Special Dental and Oral Hospital of South Sumatra Province in 2025. This research employed a quantitative analytic design with a cross-sectional approach. The sample in this study were outpatients and inpatients who had received nursing services as many as 99 respondents using the accidental sampling technique. Data were collected through questionnaires, namely assertive behavior questionnaires and patient satisfaction. Data analysis was performed using the chi-square test to identify the relationship between the two variables. The results showed a significant relationship between nurses’ assertive behavior and patient satisfaction (0.011 <0.05). The study concludes that assertive behavior among nurses plays a vital role in enhancing patient satisfaction. Therefore, it is expected that the Hospital as a service center where sick patients receive services that are full of empathy, a sense of security and comfort, uncomplicated service and good communication. This must be mastered by nurses because they are aspects of assertive behavior that nurses must apply in service.